Implementasi Pembelajaran Akidah Akhlak Dalam Pembentukan Karakter Religius Peserta Didik di MTSN 4 Pasaman Barat - Juita, Rafika; J, Januar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The research background outlines that MTsN 4 Pasaman Barat has adopted Moral Creed Learning to build student character. However, it faces challenges due to students' diverse characters, necessitating active involvement from moral creed teachers and the school environment to shape religious character collectively. The research aims to assess the implementation of Aqidah Akhlak learning in this context and identify factors that facilitate or hinder it. This study employs qualitative descriptive field research. Key informants include the Aqidah Akhlak teacher of class VII.5, supported by students, homeroom teachers, and the school principal. Data was gathered through interviews, observations, and documentation, analyzed via data reduction, display, and verification methods. Findings reveal that the implementation includes preparatory steps like open modules, appropriate learning materials, and teacher mastery. The learning process encompasses initial, core, and closing activities, beginning with greetings and communal prayers to foster religious character. Core activities involve engaging learning media aligned with the curriculum, concluding again with communal prayers. Supporting factors include competent teachers, an effective school environment, and adequate facilities. Conversely, constraints include limited time for Moral Creed Learning and student diversity. In summary, the research highlights the structured implementation of Aqidah Akhlak learning to nurture students' religious character amidst challenges and supportive elements at MTsN 4 Pasaman Barat.